Answer:
Explanation:
12x - y = -4 ----------------------(I)
4x - 3y = -6 ---------------------(II)
Multiply equation (I) by (-3)
(I)*(-3) -36x + 3y = 12
(II) 4x - 3y = - 6 {Add and y will be eliminated}
- 32x = 6
x = 6/-32
x = -3/16
Plugin the value of x in equation (I)
![12*(-3)/(16) -y=-4\\\\3*(-3)/(4)-y=-4\\\\(-9)/(4)-y = -4\\\\-y=-4+(9)/(4)\\\\-y=(-4*4)/(1*4)+(9)/(4)\\\\-y=(-16)/(4)+(9)/(4)\\\\-y=(-7)/(4)\\\\y=(7)/(4)\\\\y=1(3)/(4)](https://img.qammunity.org/2021/formulas/mathematics/college/4vjv5rhcebgd00wgt5a6fu440fvw6fajwl.png)